Gag and env conserved element CE DNA vaccines elicit broad cytotoxic T cell responses targeting subdominant epitopes of HIV and SIV Able to recognize virus-infected cells in macaques - Xintao Hu; Zhongyan Lu; Antonio Valentin; Margherita Rosati; Kate E. Broderick; Niranjan Y. Sardesai; Preston A. Marx; James I. Mullins; George N. Pavlakis; Barbara K. Felber (Taylor & Francis Group, 2018)
HIV sequence diversity and the propensity of eliciting immunodominant responses targeting inessential variable regions are hurdles in the development of an effective AIDS vaccine. We developed a DNA vaccine comprising conserved elements (CE) of SIV p27Gag and HIV-1 Env and found that priming vaccination with CE DNA is critical to efficiently overcome the dominance imposed by Gag and Env variable regions. Here, we show that DNA vaccinated macaques receiving the CE prime/CE+full-length DNA co-delivery booster vaccine regimens developed broad, potent and durable cytotoxic T cell responses targeting conserved protein segments of SIV Gag and HIV Env. Gag CE-specific T cells showed robust anamnestic responses upon infection with SIVmac239 which led to the identification of CE-specific cytotoxic lymphocytes able to recognize epitopes covering distinct CE on the surface of SIV infected cells in vivo. Though not controlling infection overall, we found an inverse correlation between Gag CE-specific CD8+ T cell responses and peak viremia. The T cell responses induced by the HIV Env CE immunogen were recalled in some animals upon SIV infection, leading to the identification of two cross-reactive epitopes between HIV and SIV Env based in sequence homology. These data demonstrate that a vaccine combining Gag and Env CE DNA subverted the normal immunodominance patterns, eliciting immune responses that included subdominant, highly conserved epitopes. These vaccine regimens augment cytotoxic T cell responses to highly conserved epitopes in the viral proteome and maximize response breadth. The vaccine-induced CE-specific T cells were expanded upon SIV infection, indicating that the predicted CE epitopes incorporated in the DNA vaccine are processed and exposed by infected cells in their natural context within the viral proteome.